Interaksionisme Simbolik Makna Piduduk Dalam Kepercayaan Masyarakat Banjar di Desa Sungai Kupang, Kabupaten Banjar - Selina Aulia Azwa; Khairussalam (Prodi Sosiologi FISIP ULM, 2023)
The Banjar community in Banjar Regency, especially in Sungai Kupang Village, has a culture that is still maintained today, namely the piduduk tradition of carrying out marriages and melabuh buaya. The purpose of this research is to find out how the implementation and meaning contained in this tradition. The method used in this research is descriptive qualitative. Data collection techniques using observation, interviews and documentation. The results of the research obtained in this study are that the piduduk tradition for marriage is carried out before the event takes place and for the piduduk melabuh buaya tradition it is held once a year. For the implementation of piduduk marriage, it can be carried out by anyone, but piduduk for melabuh buaya is only carried out by descendants. The meaning in the piduduk tradition is that both are a means of communication with supernatural beings, but the meaning in the content provided to piduduk has a different meaning. In the wedding ceremony, the contents of the piduduk are provided in the form of 3 liters of rice which is interpreted as a source of sustenance, boiled eggs which are interpreted as an element of fertility in marriage and one cup of brown sugar which is interpreted as a sweetener in husband-wife relations. The contents of piduduk in the melabuh buaya are bananas which are interpreted as crocodile teeth, sticky rice which is colored yellow is interpreted as crocodile stomachs and boiled eggs which are interpreted as crocodile navels. The conclusion is that the piduduk tradition in the beliefs of the Banjar people in Sungai Kupang Village, Banjar Regency is a tradition that has been carried out from generation to generation and is still maintained today.